2016
DOI: 10.1039/c5ra26792g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, photophysical, thermal and electrical properties of composite of polyaniline with zinc bis(8-hydroxyquinolate): a potent composite for electronic and optoelectronic use

Abstract: A novel fluorescent as well as conducting composite of polyaniline with zinc bis(8-hydroxyquinolate) complex, prepared via in situ oxidative polymerization method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The DSC of HCl and PDGDL co-doped PANI showed two endothermic transitions. The first transition, which occurred at a temperature of about 100 °C, was attributed to the loss of lattice water . The second transition that occurred at temperature of about 273 °C represented the glass transition temperature ( T g ) of polyaniline .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DSC of HCl and PDGDL co-doped PANI showed two endothermic transitions. The first transition, which occurred at a temperature of about 100 °C, was attributed to the loss of lattice water . The second transition that occurred at temperature of about 273 °C represented the glass transition temperature ( T g ) of polyaniline .…”
Section: Resultsmentioning
confidence: 99%
“…The first transition, which occurred at a temperature of about 100 °C, was attributed to the loss of lattice water. 30 The second transition that occurred at temperature of about 273 °C represented the glass transition temperature (T g ) of polyaniline. 30 Moreover, the transition temperature varied with weight ratio and polymerization time.…”
Section: Conductivity Of Protonmentioning
confidence: 99%
See 1 more Smart Citation
“…obtained by oxidative polymerization, are compared with properties of free Zn complex. 212 It is shown that doping of PA with zinc complex led to the increase in termostability and conductivity.…”
Section: Coordination Compounds Of Benzazinesmentioning
confidence: 99%
“…Polyaniline(PANI) finds widespread applications in a diversity of fields ranging across sensors [1][2][3][4], rechargeable batteries [5,6], supercapacitors [7][8][9][10], optoelectric devices [11], corrosion protection [12,13], anti-electrostatic coatings [14] and magnetic shielding [15], reflecting in part the high levels of conductivity attainable and the chemical stabilities of the material. PANI is formed by the chemical or electrochemical oxidation of aniline.…”
mentioning
confidence: 99%